Clinical application value of metagenome next-generation sequencing in pulmonary diffuse exudative lesions: a retrospective study - Wu, Yisong; Wu, Jian; Xu, Nengluan; Lin, Ming; Yue, Wenxiang; Chen, Yusheng; Zhang, Qiongyao; Li, Hongru (Frontiers in Cellular and Infection Microbiology, 2024)
Objective: This study aims to investigate the clinical application value of Metagenome Next-Generation Sequencing (mNGS) for pulmonary diffuse exudative lesions.From January 1, 2014, to November 31, 2021, 136 cases with chest radiologic presentations of pulmonary diffuse exudative lesions admitted to Fujian Provincial Hospital were included in the study; of those, 77 patients underwent mNGS pathogen detection. Based on the pathogen detection outcomes and clinical diagnoses, patients were categorized into an infection group (IG) and a non-infection group (NIG). A comparison was made between the diagnostic efficacy of the mNGS technique and traditional culture methods. Meanwhile, 59 patients clinically identified as having infectious pulmonary diffuse exudative lesions but who did not receive mNGS testing were designated as the non-NGS infection group (non-IG). A retrospective cohort study was conducted on patients in both the IG and non-IG, with a 30-day all-cause mortality endpoint used for follow-up.Outcomes: When compared to conventional culture methods, mNGS demonstrated an approximate 35% increase in sensitivity (80.0% vs 45.5%, P<0.001), without significant disparity in specificity (77.3% vs 95.5%, P=0.185). Under antibiotic exposure, the positivity rate detected by mNGS was notably higher than that by traditional culture methods, indicating that mNGS is less affected by exposure to antibiotics (P<0.05). Within 30 days, the all-cause mortality rate for patients in the IG versus the non-IG was 14.55% and 37.29%, respectively (P<0.05). Following a COX regression analysis to adjust for confounding factors, the analysis revealed that a CURB-65 score ≥3 points (HR=3.348, P=0.001) and existing cardiovascular disease (HR=2.473, P=0.026) were independent risk factors for these patients. Conversely, mNGS testing (HR=0.368, P=0.017) proved to be an independent protective factor.mNGS technology makes it easier to pinpoint the cause of pulmonary diffuse infectious exudative lesions without much interference from antibiotics, helping doctors spot and diagnose these issues early on, thereby playing a key role in helping them decide the best treatment approach for patients. Such conclusions may have a bias, as the performance of traditional methods might be underestimated due to the absence of complete results from other conventional diagnostic techniques like serological testing and PCR.